Strategies to control Staphylococcus epidermidis biofilms - Gomes, F. I. (2011)
Staphylococcus epidermidis is the staphylococci species most commonly associated with bacteremia and hospital-acquired infections and has recently arisen as the leading cause of infections related to indwelling medical devices such as vascular catheters, prosthetic joints and artificial heart valves. The prevalence of S. epidermidis in hospital-acquired infections is due to its ability to adhere and form biofilms on biomaterial surfaces. This feature is one of the most important virulence factors found in S. epidermidis. In biofilm form, bacteria are protected from antimicrobial agents and the host immune system contributing to the persistence of biofilm infections. In addition, the emergence of S. epidermidis resistance to conventional therapies, based in the use of traditional antibiotics, leads to the failure of the current treatments used in the combat of S. epidermidis infections and is becoming a major concern. These facts are stimulating the continuous search for novel agents able to eradicate S. epidermidis biofilm infections or that can work in synergy with the currently available antimicrobial agents. New strategies have been showing encouraging in vitro results in controlling S. epidermidis biofilms and seem to be promising alternatives to standard antibiotics usually used in the treatment of S. epidermidis related infections.